Supplementation of bone marrow aspirate-derived platelet-rich plasma for treating radiation-induced ulcer after cardiac fluoroscopic procedures: A preliminary report - Nishimoto, Soh; Fukuda, Kenji; Kawai, Kenichiro; Fujiwara, Toshihiro; Tsumano, Tomoko; Fujita, Kazutoshi; Kakibuchi, Masao (Indian Journal of Plastic Surgery, 2012)
Background: The frequency of encountering radiodermatitis caused by X-ray fluoroscopic procedures for ischaemic heart disease is increasing. In severe cases, devastating ulcers with pain, for which conservative therapy is ineffective, emerge. Radiation-induced ulcers are notorious for being difficult to treat. Simple skin grafting often fails because of the poor state of the wound bed. A vascularized flap is a very good option. However, the non-adherence of the well-vascularized flap with the irradiated wound bed is frequently experienced. Aim: To ameliorate the irradiated wound bed, bone marrow-derived platelet-rich plasma (bm-PRP) was delivered during the surgery. Materials and Methods: Four patients with severe cutaneous radiation injury accompanied by unbearable pain after multiple fluoroscopic procedures for ischaemic heart disease were treated. Wide excision of the lesion and coverage with a skin flap supplemented with bm-PRP injection was performed. Results: All patients obtained wound closure and were relieved from pain. No complication concerning the bone marrow aspiration and delivery of bm-PRP was observed. Conclusions: Supplementation of bm-PRP can be an option without major complications, time, and cost to improve the surgical outcome for irradiated wounds.
Keywords: Bone marrow; cardiac fluoroscopy; platelet-rich plasma; radiation ulcer; skin flap